A 2 Years Retrospective Study of Spectrum of Poisoning in a Tertiary Care Centre in Karnataka - Lohith Kumar; C. Yogesh; Naik C.R. (Indian Journal of Forensic Medicine and Pathology, 2026)
Background: Poisoning remains a major public health and medico-legal problem worldwide, particularly in developing countries where toxic substances are easily accessible. The pattern of poisoning varies with geographical, occupational and socio-economic factors. Objectives: To determine the proportion of poisoning deaths among all medicolegal autopsies and to analyze the spectrum of poisons responsible for mortality at a tertiary care centre in Chikkamagaluru. Materials and Methods: A retrospective descriptive study was conducted on medico-legal autopsies performed over a period of two years from January 2023 to December 2024 at a tertiary care centre in Chikkamagaluru. Autopsy records, police inquest reports and chemical analysis reports were reviewed. Cases where poisoning was established as the cause of death were analyzed, and data was expressed as frequencies and percentages. Results: Out of a total of 665 medico-legal autopsies, 100 cases (15.03%) were deaths due to poisoning. Organophosphous compounds were the most common poisons implicated, followed by paraquat, pyrethroid and glyphosate. In a significant proportion of cases, the chemical analysis report was negative or inconclusive. Agricultural pesticides constituted the majority of poisoning deaths. Conclusion: Poisoning accounts for a substantial proportion of medico-legal deaths in the region with agricultural pesticides being the predominant agents. Strengthening regulatory measures, improving public awareness and ensuring early medical intervention may help reduce poisoning-related mortality.